Changes in the Left Ventricular Eicosanoid Profile in Human Dilated Cardiomyopathy - Sosnowski, Deanna K.; Jamieson, K. Lockhart; Darwesh, Ahmed M.; Zhang, Hao; Keshavarz-Bahaghighat, Hedieh; Valencia, Robert; Viveiros, Anissa; Edin, Matthew L.; Zeldin, Darryl C.; Oudit, Gavin Y.; Seubert, John M. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Metabolites derived from N-3 and N-6 polyunsaturated fatty acids (PUFAs) have both beneficial and detrimental effects on the heart. However, contribution of these lipid mediators to dilated cardiomyopathy (DCM)-associated mitochondrial dysfunction remains unknown. This study aimed to characterize DCM-specific alterations in the PUFA metabolome in conjunction with cardiac mitochondrial quality in human explanted heart tissues. Methods: Left ventricular tissues obtained from non-failing control (NFC) or DCM explanted hearts, were assessed for N-3 and N-6 PUFA metabolite levels using LC-MS/MS. mRNA and protein expression of CYP2J2, CYP2C8 and epoxide hydrolase enzymes involved in N-3 and N-6 PUFA metabolism were quantified. Cardiac mitochondrial quality was assessed by transmission electron microscopy, measurement of respiratory chain complex activities and oxygen consumption (respiratory control ratio, RCR) during ADP-stimulated ATP production. Results: Formation of cardioprotective CYP-derived lipid mediators, epoxy fatty acids (EpFAs), and their corresponding diols were enhanced in DCM hearts. These findings were corroborated by increased expression of CYP2J2 and CYP2C8 enzymes, as well as microsomal and soluble epoxide hydrolase enzymes, suggesting enhanced metabolic flux and EpFA substrate turnover. DCM hearts demonstrated marked damage to mitochondrial ultrastructure and attenuated mitochondrial function. Incubation of fresh DCM cardiac fibres with the protective EpFA, 19,20-EDP, significantly improved mitochondrial function. Conclusions: The current study demonstrates that increased expressions of CYP-epoxygenase enzymes and epoxide hydrolases in the DCM heart correspond with enhanced PUFA-derived EpFA turnover. This is accompanied by severe mitochondrial functional impairment which can be rescued by the administration of exogenous EpFAs.